Observations and spectral modelling of the narrow-lined Type Ic SN 2017ein. Issue 3 (30th January 2021) - Teffs, J J; Prentice, S J; Mazzali, P A; Ashall, C
ABSTRACT: SN 2017ein is a narrow-lined Type Ic SN that was found to share a location with a point-like source in the face on spiral galaxy NGC 3938 in pre-supernova images, making SN 2017ein the first credible detection of a Type Ic progenitor. Results in the literature suggest that this point-like source is likely a massive progenitor of 60–80 M⊙, depending on if the source is a binary, a single star, or a compact cluster. Using new photometric and spectral data collected for 200 d, including several nebular spectra, we generate a consistent model covering the photospheric and nebular phase using a Monte Carlo radiation transport code. Photospheric phase modelling finds an ejected mass 1.2–2.0 M⊙ with an E k of ∼(0.9 ± 0.2) × 10 51 erg, with approximately 1 M⊙ of material below 5000 km s −1 found from the nebular spectra. Both photospheric and nebular phase modelling suggests a 56 Ni mass of 0.08–0.1 M⊙ . Modelling the [O i ] emission feature in the nebular spectra suggests that the innermost ejecta are asymmetric. The modelling results favour a low-mass progenitor of 16–20 M⊙,  which is in disagreement with the pre-supernova derived high-mass progenitor. This contradiction is likely due to the pre-supernova source not representing the actual progenitor.